A Brief Review on Particle Acceleration in Multi-island Magnetic Reconnection. (November 2019) - Che, H.; Zank, G. P.
Abstract: The basic physics and recent progresses in theoretical and particle-in-cell (PIC) simulation studies of particle acceleration in multi-island magnetic reconnection are briefly reviewed. Particle acceleration in multi-island magnetic reconnection is considered a plausible mechanism for the acceleration of energetic particles in solar flares and the solar wind. Theoretical studies have demonstrated that such a mechanism can produce the observed power- law energy distribution of energetic particles if the particle motion is sufficiently randomized in the reconnection event. However, PIC simulations seem to suggest that the first-order Fermi acceleration mechanism is unable to produce a power-law particle energy distribution function in mildly relativistic multi-island magnetic reconnections. On the other hand, while simulations of highly relativistic reconnections appear to be able to produce a power-law energy spectra, the spectral indices obtained are generally harder than the soft power-law spectra with indices ~ − 5 commonly observed in the solar wind and solar flare events. In addition, the plasma heating due to kinetic instabilities in 3D magnetic reconnection may "thermalize" the power-law particles, making it even more difficult for multi-island reconnections to generate a power-law spectrum. We discuss the possible reasons that may lead to these problems.